CAMPUS-BASED STRATEGIES TO ADDRESS SUICIDE BEHAVIOURS AMONGST STUDENTS AT INSTITUTIONS OF HIGHER LEARNING IN SOUTH AFRICA: A NARRATIVE REVIEW. - Chuene, Tiisetso Aubrey; Kgarose, Mathibedi Frank (Student's Journal of Health Research Africa, 2024)
Suicide rates among adolescents and youth are increasing regardless of the interventions to lower the risks. Therefore, preventing suicides at institutions of higher learning is a top concern for public mental health. This paper explores strategies that may be adopted to reduce suicidal thoughts among students in South Africa. The study analyzed previously published data on student suicide at institutions of higher learning. The purposive sampling technique was used by the researchers to collect secondary data from various research platforms that were specifically focused on the topic at hand. A non-empirical research design was used where information from Google Scholar, Jstor, EbscoHost, Proquest, Scopus, and Sabinet were sampled and reviewed using keywords and phrases related to suicide, strategies, and behaviors to filter relevant data. This review highlights that there are a variety of causes for students' suicidal thoughts, and these causes are individualized. Suicide prevention strategies such as gatekeeper training programs for suicidal behaviors, implementation of suicide prevention awareness programs within campuses, digitalization of the programs, counseling, and psychotherapy are some of the strategies that universities can adopt to reduce suicidal thoughts among students. Given the complexity of suicide, prevention must be done with extreme prudence and urgency. The more the complexity of the suicide process is understood, the more the need for consistent, significant efforts to empirically support and evaluate the prevention strategies. It is therefore imperative to implement comprehensive and multi-sector preventative programs to minimize these risk factors and enhance protective variables to the greatest extent possible.